Hipparchus’ didactic journey: Poetry, prose and catalogue form in the 'Commentary on Aratus and Eudoxus' - Lightfoot, J (Duke University, 2017)
Seeking to establish his didactic superiority to prior commentators on the astronomers, Hipparchus hit upon the catalogue form as expressing his views in the most authoritative way.